A practitioners’ guide to applying The Nature Conservancy’s Voice, Choice, and Action framework for community-based management of freshwater resources - CGIAR Research Program on Water, Land and Ecosystems (2020)
This guide aims to advance the understanding of how communities can sustainably manage freshwater resources by applying The Nature Conservancy’s Voice, Choice, and Action framework. The original framework focused more on terrestrial resources but has been adapted here to address the unique characteristics of freshwater resources.